Evaluation of visual evoked potentials in type II diabetes mellitus subjects attending a tertiary care hospital - V., Gowri (International Journal of Research in Medical Sciences, 2018)
Background: DM is the most common metabolic disorder in the world. The complications of DM take millions of lives every year. There is definite expectation to reason out both vasculopathy and neuropathy associated with DM leads to dysfunction along the visual pathway. The Visual Evoked Potentials (VEPs) as an electrophysiological method to assess conduction in type II DM subjects which is simple. This study attempted to detect earlier visual involvement before the clinical symptoms. Methods: VEP was recorded in 100 subjects (Diabetic 50 and Controls 50) P100 latency was compared between the diabetic and age, gender matched controls. Results: The study evidenced that the mean P 100 latency in DM subjects was found to be significantly prolonged when compared the that of controls. Conclusions: The study will help in supervising the earlier progress of neuropathy and earlier detection of nervous system involvement to reduce the morbidity of the diabetic subject and a special care to improve their quality of life.